Comparison of measurement overflows with flumes - Dąbrowski, Wojciech (Instal, 2022)
The usefulness of flumes and sharp-edged overflows in the measurements of flows in sewerage systems is compared. The conflict of the accuracy with the reliability of the measurements carried out with the use of flumes is presented. Imperfections of the ISO 4359 standard relating to rectangular, trapezoidal U-shaped flumes is described